Strategic Policy Competition with Public Infrastructure - Richard Nahuis; Paul J.G. Tang (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2004)
Governments try to attract firms and jobs by investing in international infrastructure. We analyse this type of strategic policy competition in a three-country model of monopolistic competition. What governments compete for, is to obtain a so called 'hub' position. A hub is a relatively well connected location in a transport network. A hub might thus be an attractive location for firms. However, for a small or backward country the hub position, due to infrastructure investment, is overwhelmed by the disadvantage of a small home-market. As investment to become a hub triggers an investment response from other countries, a backward country is unlikely to keep its relatively attractive position. An attractive location is only sustainable if investment applies to point infrastructure and builds upon a natural advantage (e.g. an harbour). The game of action and reaction delivers socially undesirably high levels of infrastructure investment if transport costs are already low and firm mobility is high.
Keywords: 330; Infrastructure; Industrial Location; Policy Competition; Monopolistic Competition; International Trade